2020
DOI: 10.3758/s13414-019-01961-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleaved lexical and audiovisual information can retune phoneme boundaries

Abstract: To adapt to situations in which speech perception is difficult, listeners can adjust boundaries between phoneme categories using perceptual learning. Such adjustments can draw on lexical information in surrounding speech, or on visual cues via speechreading. In the present study, listeners proved they were able to flexibly adjust the boundary between two plosive/stop consonants, /p/-/t/, using both lexical and speech-reading information and given the same experimental design for both cue types. Videos of a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…The perceptual boundary between two phonemes, /p/ and /t/, was systematically shifted, using lexical and audiovisual cues, toward either /p/ or /t/. Note that the behavioral results had shown that this procedure resulted in significant effects in both conditions and toward both phonemes, although audiovisual recalibration effects were larger than lexical retuning, in line with previous findings as well (Ullas et al, 2020a;van Linden & Vroomen, 2007). The analysis of concurrent fMRI measurements showed similarities between audiovisual and lexical exposure blocks, particularly in the temporal cortex across bilateral HG, STG/STS, and PT as well as left IPL and right insula.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The perceptual boundary between two phonemes, /p/ and /t/, was systematically shifted, using lexical and audiovisual cues, toward either /p/ or /t/. Note that the behavioral results had shown that this procedure resulted in significant effects in both conditions and toward both phonemes, although audiovisual recalibration effects were larger than lexical retuning, in line with previous findings as well (Ullas et al, 2020a;van Linden & Vroomen, 2007). The analysis of concurrent fMRI measurements showed similarities between audiovisual and lexical exposure blocks, particularly in the temporal cortex across bilateral HG, STG/STS, and PT as well as left IPL and right insula.…”
Section: Discussionsupporting
confidence: 90%
“…The phoneme bias of the exposure block alternated every two blocks. Although this procedure can successfully result in both audiovisual and lexical retuning effects, audiovisual cues, compared to lexical, can lead to larger effects (Ullas et al, 2020a; Figure 1).…”
Section: Behavioral Proceduresmentioning
confidence: 99%
See 3 more Smart Citations